1302 Development of a portable analyzer for on-site biomonitoring of workers exposed to respirable crystalline silica. (24th April 2018) - Ku, Bon Ki; Vinitha, TU; Birch, ME; Ahn, Chong H
Abstract : Introduction: Respirable crystalline silica (RCS) exposure is considered as one of the most significant occupational health problems in the United States. Recent National Institute for Occupational Safety and Health (NIOSH) field studies identified overexposure to RCS in oil and gas extraction workers, with exposures exceeding occupational RCS exposure levels by factors of 20 or more in sand moving and transfer belt operations. To facilitate on-site screening of workers to identify early (i.e., preclinical) biological responses to RCS exposure, there is a strong need for field-portable diagnostic instruments and methods, particularly for workers in mining, oil and gas extraction, and construction industries. Methods: A portable analyzer for on-site biomonitoring using a lab-on-a-chip (LOC) device was developed, and its performance in measurement of an inflammatory biomarker for inhalation of RCS aerosol was evaluated. Results: The overall performance of the portable analyzer with the LOC device had accuracy and precision comparable to laboratory testing results. It runs on a LabView-based program that controls variable parameters: on/off sequence, reagent flow speed, pump run time and optical detection. The pump input to the LOC and a portable analyzer are coupled to the LOC device with PEEK tubing, for automated ELISA testing in the field. Conclusion: This is the first field-portable analyzer capable of on-site screening of workers to identify early (i.e., preclinical) biological responses to RCS exposure. Our work supports application of the analyzer together with the developed LOC as a portable monitor for on-site detection of lung inflammation in workers exposed to RCS, with minimum user intervention. Development of a device for detecting exposure-related biomarkers of biological processes (e.g., inflammation) that are predictive of the pathogenicity of exposure to RCS and other airborne toxicants would offer an important new approach for silicosis prevention.